Information System for the Goods Transport Service Network - Holm, Caj; Kallstorm, Lars; Šafran, Mario (Promet - Traffic&Transportation, 2008)
Intermodal transport can reduce the load of the road infrastructure.Knowledge gives it the necessary competitiveness andhelps to control its costs. Fast reaction to changing conditions,opportunities and requirements gives remarkable advantage.Setting up integrated logistic chains using alternative transportmodes requires the trust and close interaction of a variety of actorsinvolved in managing the chain. Especially in the dynamicmobile environment, knowledge has so far not been effectivelyused. FREIGHTWISE tackles this complexity by developing aframework architecture anchored and validated in a range ofdemonstration cases involving commercial and public actors.This paper discusses the general FREIGHTWISE objectivesand its North-East Case, the Logistiikkainfo goods transportservice network information system to be implemented for theEstonian - Finnish transport chain.